Heat and Work Along Individual Trajectories of a Quantum Bit - Naghiloo, M.; Tan, D.; Harrington, P. M.; Alonso Castaneda, Jose Joaquin; Lutz, E.; Romito, A.; Murch, K. W. (Physical Review Letters, 2020)
We use a near quantum limited detector to experimentally track individual quantum state trajectories of a driven qubit formed by the hybridization of a waveguide cavity and a transmon circuit. For each measured quantum coherent trajectory, we separately identify energy changes of the qubit as heat and work, and verify the first law of thermodynamics for an open quantum system. We further establish the consistency of these results by comparison with the master equation approach and the two-projective-measurement scheme, both for open and closed dynamics, with the help of a quantum feedback loop that compensates for the exchanged heat and effectively isolates the qubit.
CRIS-Team WoS Importer:2020-04-07

Thermodynamics of continuous non-Markovian feedback control - Debiossac, Maxime; Grass, David; Alonso Castaneda, Jose Joaquin; Lutz, Eric; Kiesel, Nikolai (Nature Communications, 2020)
Feedback control mechanisms are ubiquitous in science and technology, and play an essential role in regulating physical, biological and engineering systems. The standard second law of thermodynamics does not hold in the presence of measurement and feedback. Most studies so far have extended the second law for discrete, Markovian feedback protocols; however, non-Markovian feedback is omnipresent in processes where the control signal is applied with a non-negligible delay. Here, we experimentally investigate the thermodynamics of continuous, time-delayed feedback control using the motion of an optically levitated, underdamped microparticle. We test the validity of a generalized second law which bounds the energy extracted from the system, and study the breakdown of feedback cooling for very large time delays.
CRIS-Team Scopus Importer:2020-03-27